Polar organic solvent solution of ammonium styrenesulfonate with spontaneous polymerization suppressed and method for producing ammonium styrenesulfonate copolymer using the solution
By controlling the concentrations of water and organic polymerization inhibitors in the polar organic solvent solution, the spontaneous polymerization of ammonium styrene sulfonate is suppressed, facilitating efficient and reproducible copolymerization with oil-soluble vinyl monomers, producing high-quality copolymers.
Patent Information
- Application Number
- JP2024065839
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-13
- Filing Date
- 2024-04-16
- Publication Date
- 2025-01-24
AI Technical Summary
The spontaneous polymerization of ammonium styrene sulfonate (AMSS) in polar organic solvents before the polymerization process, leading to inefficient copolymerization and poor reproducibility, is a significant challenge due to its high solubility and instability in these solvents.
A polar organic solvent solution of ammonium styrene sulfonate is formulated with specific concentrations of water, aliphatic amine, and organic polymerization inhibitors to suppress spontaneous polymerization, allowing for efficient copolymerization with oil-soluble vinyl monomers.
The solution effectively prevents spontaneous polymerization, enabling stable and reproducible copolymerization processes, resulting in high-quality copolymers with controlled molecular weights and improved solubility parameters.
Smart Images

Figure 2025013156000010 
Figure 2025013156000011 
Figure 2025013156000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a polar organic solvent solution of ammonium styrenesulfonate in which spontaneous polymerization is efficiently suppressed without containing a high concentration of a polymerization inhibitor, and to a method for producing an ammonium styrenesulfonate copolymer using the solution. [Background technology]
[0002] Styrene sulfonate is a strong electrolyte-type water-soluble monomer with surface activity, and because it has excellent heat resistance and radical polymerization properties, it is used as a reactive emulsifier for emulsion polymerization, and has long been used as a raw material for producing aqueous dispersants, aqueous detergents, and dopants for conductive polymers, etc. Sodium styrene sulfonate (hereinafter abbreviated as NaSS) is widely used industrially, but its applications are limited because it has poor solubility in organic solvents and contains alkali metals.
[0003] Therefore, lithium styrene sulfonate (hereinafter abbreviated as LiSS), which is highly soluble in organic solvents, was developed. Although LiSS is an alkali metal salt, it dissolves at high concentrations in polar organic solvents such as N-methylpyrrolidone, and can be copolymerized by adding divinylbenzene, an oil-soluble cross-linkable vinyl monomer, and therefore has been put to practical use as a simple method for producing cation exchange membranes (e.g., Patent Documents 1 and 2). However, since it contains an alkali metal, its applications are still limited, and there is also the issue of rising raw material prices due to the recent expansion of demand for lithium secondary batteries.
[0004] In light of the above, ammonium styrenesulfonate (hereinafter abbreviated as AmSS), which does not contain alkali metals and is soluble in polar organic solvents, has long been attracting attention (e.g., Non-Patent Document 1), but there are significant issues with the production method and storage stability, and it has not been industrialized. Therefore, the present inventors have continued to study the production method and properties of AmSS, and as a result, have found a simple production method for AmSS with good storage stability.
[0005] AmSS is expected to be used as a raw material for pigment dispersants for color filters (e.g., Patent Document 3) and hard coat agents for optical materials (e.g., Patent Document 4), as well as for electronic material applications where metal content is undesirable, as a substitute for expensive LiSS. In these applications, an AmSS copolymer is produced by homogeneously dissolving an acidic group-containing vinyl monomer such as AmSS and an oil-soluble vinyl monomer such as a styrene or methacrylic acid ester in a polar organic solvent such as a glycol ether, an ester, or N-methylpyrrolidone, and copolymerizing the monomer. In this case, AmSS may contain impurities derived from raw materials that are insoluble in polar organic solvents, such as alkali metal salts, ammonium salts, or AmSS polymers, so after dissolving AmSS in a polar organic solvent, the solution is usually filtered before being used for copolymerization. However, there is an issue that AmSS spontaneously polymerizes in the process prior to the polymerization process, i.e., the process prior to the addition of the polymerization initiator, despite the presence of organic polymerization inhibitors derived from AmSS at levels exceeding several tens of ppm, and a solution was strongly desired.
[0006] In addition, since AmSS was hardly distributed on the market, there were few reports on the copolymerization of AmSS and oil-soluble vinyl monomers in polar organic solvents. As a result of the inventors' investigation of the (co)polymerization of AmSS in polar organic solvents, it was found that AmSS exhibits the same solubility as LiSS in polar organic solvents such as N-methylpyrrolidone, but when AmSS is homopolymerized or AmSS is copolymerized with styrenes in the solvent, the polymer precipitates at the early stage of polymerization, and it is not possible to (co)polymerize AmSS like LiSS. Therefore, there has been a strong demand for a method that can copolymerize AmSS and oil-soluble vinyl monomers in a polar organic solvent at as high a concentration as possible. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] U.S. Patent No. 6,221,248 [Patent Document 2] Patent No. 7386705 [Patent Document 3] Patent No. 5924282 [Patent Document 4] JP 2016-79363 A [Non-patent literature]
[0008] [Non-Patent Document 1] Oriental Soda Research Report, Vol. 24, No. 1, 1980, pp. 3-11. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in view of the above background and problems, and an object of the present invention is to provide a polar organic solvent solution of ammonium styrenesulfonate in which spontaneous polymerization is suppressed to an extent that does not adversely affect the polymer production process, such as copolymerization reactivity, molecular weight of the copolymer, and reproducibility thereof, and a method for producing an ammonium styrenesulfonate copolymer using the solution. [Means for solving the problem]
[0010] The present inventors have investigated the physical properties of ammonium styrenesulfonate (hereinafter abbreviated as AmSS) in detail, and as a result, have found that, like sodium styrenesulfonate (hereinafter abbreviated as NaSS) and lithium styrenesulfonate (hereinafter abbreviated as LiSS), ammonium styrenesulfonate is stable in an aqueous solution and does not easily undergo spontaneous polymerization, but is highly susceptible to unintended spontaneous polymerization (also referred to as spontaneous polymerization or non-catalytic polymerization) particularly in basic polar organic solvents such as N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and 1,3-dimethyl-2-imidazolidinone, and further that the spontaneous polymerization proceeds via a radical mechanism, and occurs in either an atmosphere of air or an inert gas such as nitrogen, and in the dark. In addition, AmSS exhibits solubility in polar organic solvents such as N-methylpyrrolidone equivalent to that of LiSS. However, it was found that when AmSS is polymerized in such a solvent or when AmSS is copolymerized with an oil-soluble monomer, the polymer precipitates and the desired product cannot be obtained. In this specification, the spontaneous polymerization mentioned above means "spontaneous polymerization" (see Aoki Shuzo, "Review: Spontaneous Polymerization in Micelles as a Reaction Field", Journal of the Society of Organic Synthesis, Vol. 53, No. 5 (1995)) or "non-catalytic polymerization" (see Ogawa et al., "Non-catalytic polymerization of sodium ethylenesulfonate", Polymer Research Papers, Vol. 74, No. 2, pp. 134-138 (Mar., 2017)).
[0011] As a result of intensive research to solve the above problems, the present inventors have found that when a polar organic solvent solution of AmSS contains a specific concentration of water, an aliphatic amine, and an organic polymerization inhibitor, the spontaneous polymerization of AmSS can be effectively suppressed. Furthermore, the present inventors have found that an AmSS copolymer can be efficiently produced by precisely controlling the solvent composition of the AmSS solution and then copolymerizing it by adding an oil-soluble vinyl monomer and a polymerization initiator, and have thus completed the present invention.
[0012] That is, the present invention relates to the following inventions. [1] Ammonium styrenesulfonate, Water content of 300.0 mol% or less relative to ammonium styrenesulfonate; 20 mol % or less of an aliphatic amine relative to ammonium styrenesulfonate; 0.500 mol % or less of an organic polymerization inhibitor relative to ammonium styrenesulfonate; A polar organic solvent solution of ammonium styrenesulfonate, the spontaneous polymerization of which is inhibited, comprising: [2] Ammonium styrenesulfonate, Water of 100.0 mol% to 300.0 mol% relative to ammonium styrenesulfonate; 20.0 mol % or less of an aliphatic amine relative to ammonium styrenesulfonate; 0.0020 mol % to 0.500 mol % of an organic polymerization inhibitor relative to ammonium styrenesulfonate; The solution according to item [1], comprising: [3] Ammonium styrenesulfonate, Water content of 300.0 mol% or less relative to ammonium styrenesulfonate; 1.0 mol % to 20.0 mol % of an aliphatic amine relative to ammonium styrenesulfonate; 0.500 mol % or less of an organic polymerization inhibitor relative to ammonium styrenesulfonate; The solution according to item [1], comprising: [4] The solution according to item [1], wherein the content of ammonium styrenesulfonate is 20.0% by weight to 45.0% by weight based on the total amount of the solution. [5] The solution according to item [1], wherein the content of polymer due to spontaneous polymerization is 0.5% by weight or less. [6] The solution according to item [1], wherein the polar organic solvent has the following Hansen solubility parameters (a) to (c) in the following ranges. (a) Dispersion term δ d =16.5~18.5MPa 1 / 2 (b) Polarization term δ p =11.5~16.5MPa 1 / 2 (c) Hydrogen bond term δ h = 7.0~12.5MPa 1 / 2 [7] The solution according to item [1], wherein the polar organic solvent contains 80% by weight or more of one or more organic solvents selected from the group consisting of N-methylpyrrolidone, N-ethyl-2-pyrrolidone, dimethylsulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and 1,3-dimethyl-2-imidazolidinone. [8] The solution according to item [1], wherein the organic polymerization inhibitor is a phenol-based polymerization inhibitor and / or a stable nitroxyl-based polymerization inhibitor. [9] The solution according to item [1], wherein the aliphatic amine is an aliphatic amine having 8 or less carbon atoms.
[10] The organic polymerization inhibitor is 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 4-ethoxyphenol, 4-cyanophenol, 4-butoxyphenol, 3-ethoxyphenol, 2,5-dimethoxyphenol, 2,6-dimethoxyphenol, 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 4-tert-butylcatechol, hydroquinone, methylhydroquinone, 2-methoxyhydrazine, The solution according to item [1], which is one or more polymerization inhibitors selected from the group consisting of 2,2,6,6-tetramethylpiperidine 1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, 4-(2-hydroxypropoxy-3-(2-hydroxyethoxy))-2,2,6,6-tetramethylpiperidin-1-ol, and 4-(3-hydroxypropoxy-2-(2-hydroxyethoxy))-2,2,6,6-tetramethylpiperidin-1-ol.
[11] The solution according to item [1], wherein the aliphatic amine is one or more aliphatic amines selected from the group consisting of 2-hydroxyethylamine, diethylamine, diethanolamine, N-methylethanolamine, N-methyl-N,N-diethanolamine, piperidine, morpholine, N-methylpiperazine, triethylamine, triethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dimethylcyclohexylamine, N-methylpiperidine, N-methylmorpholine, N-ethylmorpholine, and 2-[(2-dimethylamino)ethoxy]ethanol.
[12] In a polar organic solvent solution of ammonium styrenesulfonate used in the polymerization process of ammonium styrenesulfonate, The water content of ammonium styrenesulfonate is 300.0 mol% or less. 20.0 mol% or less of aliphatic amine relative to ammonium styrenesulfonate; The organic polymerization inhibitor for ammonium styrenesulfonate is 0.500 mol% or less. A method for suppressing spontaneous polymerization of ammonium styrene sulfonate.
[13] A solvent different from the polar organic solvent contained in the solution of ammonium styrenesulfonate is added to the polar organic solvent solution to obtain a solvent composition having the following Hansen solubility parameters (d) to (f) in the following ranges, and then an oil-soluble vinyl monomer and a polymerization initiator are added to carry out radical copolymerization. Or, An oil-soluble vinyl monomer and a polymerization initiator are added to a polar organic solvent solution of ammonium styrenesulfonate, and then a solvent different from the polar organic solvent contained in the solution is added to obtain a solvent composition having the following Hansen solubility parameters (d) to (f) in the following ranges, and then radical copolymerization is performed. Method for producing ammonium styrene sulfonate copolymer. (d) Dispersion term δ d =17.5~18.5MPa 1 / 2 (e) Polarization term δ p =12.0~16.5MPa 1 / 2 (f) Hydrogen bond term δ h = 8.5~12.5MPa 1 / 2
[14] The method according to item
[13] , wherein the solvent other than the polar organic solvent is one or more solvents selected from the group consisting of ethylene glycol, propylene glycol, glycerin, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, methoxyethanol, ethoxyethanol, 1-methoxy-2-propanol, propylene glycol monomethyl ether, dioxane, dihydrolevoglucosenone, dimethoxyethane, triethanolamine, acetone, acetonitrile, and water.
[15] The method for producing the ammonium styrene sulfonate AmSS copolymer according to item
[13] , wherein the oil-soluble vinyl monomer is one or more monomers selected from the group consisting of styrenes, acrylic esters, methacrylic esters, and maleimides. Effect of the Invention
[0013] The polar organic solvent solution of AmSS of the present invention contains specific concentrations of water, aliphatic amine, and organic polymerization inhibitor, which suppresses the problem of spontaneous polymerization before the polymerization step, which was a conventional issue. Furthermore, after optimizing the solvent composition of the AmSS solution, an oil-soluble vinyl monomer and a polymerization initiator are added to carry out copolymerization, making it possible to efficiently produce an AmSS copolymer. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 shows a dissolution curve (enlarged view) of the AmSS solution measured by GPC after aging at 25° C. for 3 days in Comparative Example 1, in which the X-axis (horizontal axis) indicates the dissolution time (unit: minutes) and the Y-axis (vertical axis) indicates the UV (230 nm) absorption peak area (unit: %). [Diagram 2] FIG. 1 shows a dissolution curve (enlarged view) of the AmSS solution measured by GPC after aging at 25° C. for 14 days in Example 1, in which the X-axis (horizontal axis) indicates the dissolution time (unit: minutes) and the Y-axis (vertical axis) indicates the UV (230 nm) absorption peak area (unit: %). [Diagram 3] 1 shows the polymerization conversion rate of AmSS (black circles) and styrene (black triangles) in Example 1, with the X-axis (horizontal axis) representing the polymerization time (unit: hours) and the Y-axis (vertical axis) representing the polymerization conversion rate. [Figure 4] 1 shows a GPC molecular weight distribution curve of the copolymer obtained in Example 14, in which the horizontal axis represents the natural logarithm of the molecular weight and the vertical axis represents the UV (wavelength 230 nm) absorption peak intensity (arbitrary units). [Diagram 5] 1 shows a GPC molecular weight distribution curve of the copolymer obtained in Example 15, in which the horizontal axis represents the natural logarithm of the molecular weight and the vertical axis represents the UV (wavelength 230 nm) absorption peak intensity (arbitrary units). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. Styrene sulfonates are anionic monomers with surface activity, and examples of such salts include sodium styrene sulfonate (hereinafter abbreviated as NaSS), lithium styrene sulfonate (hereinafter abbreviated as LiSS), and ammonium styrene sulfonate (hereinafter abbreviated as AmSS). Of these, LiSS and AmSS, which are highly soluble in polar organic solvents, are expected to be used in applications that cannot be handled by NaSS, which has low solubility, and AmSS, which has a reduced metal content, is expected to be used in the electronic materials field. However, when preparing a solution of AmSS in a polar organic solvent, a problem occurred in which AmSS spontaneously polymerized before the polymerization process (before the polymerization initiator was added), such as during the dissolution process or the filtration process of the solution, and a solution was needed.
[0016] Incidentally, spontaneous polymerization in polar organic solvents has already been observed for LiSS. Detailed investigations of spontaneous polymerization revealed that LiSS is extremely stable in aqueous solutions and does not spontaneously polymerize easily, but in polar organic solvents, particularly basic polar organic solvents such as dimethyl sulfoxide, N-methyl-2-pyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide, it is essentially prone to spontaneous polymerization, even in the dark and in an atmosphere of either air or inert gas such as nitrogen. Furthermore, it was found that spontaneous polymerization in polar organic solvents cannot be suppressed by common inorganic polymerization inhibitors such as sodium nitrite and lithium nitrite, but can be strongly suppressed by organic polymerization inhibitors such as 4-methoxyphenol. Although the initiating species is unclear, it is speculated that the spontaneous polymerization proceeds via a radical mechanism, and that the aggregation state of LiSS molecules in polar organic solvents is involved.
[0017] As a result of further investigations, the inventors found that spontaneous polymerization of LiSS can be efficiently suppressed when a polar organic solvent solution of LiSS does not contain a high concentration of polymerization inhibitor, but contains a specific concentration of water or water and lithium bromide, and filed a patent application (JP Patent Publication No. 2022-25184). Although the mechanism of stabilization by water is not necessarily clear, the specific aggregation state of LiSS molecules in a polar organic solvent is the largest among various solvents in terms of the hydrogen bond term δ of the solubility parameter. h It was speculated that the polymerization inhibition effect of lithium bromide is due to bromine radicals generated by the oxidation of bromide ions, and that the more water there is, the greater the degree of ionic dissociation of lithium bromide, making it easier for bromine radicals to be generated.
[0018] Since AmSS was also stable in aqueous solution, we speculated that the aggregation state of AmSS molecules in polar organic solvents was involved in the spontaneous polymerization, as in LiSS. However, the spontaneous polymerization of AmSS was much stronger than that of LiSS, and the spontaneous polymerization could not be prevented by water or lithium bromide. Since spontaneous polymerization proceeds by a radical mechanism, the polymerization inhibition effect of organic polymerization inhibitors was clear, but it was found that the addition of about 30 ppm, which was a significant effect for LiSS, could not inhibit the spontaneous polymerization at all. Considering the polymerization process after filtering the polar organic solvent solution of AmSS, i.e., the effect on the polymerization and the molecular weight of the copolymer, and the reproducibility of these, a method to efficiently inhibit the spontaneous polymerization with as low a concentration of polymerization inhibitor as possible was required.
[0019] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by controlling the water content, aliphatic amine, and organic polymerization inhibitor in a polar organic solvent solution of AmSS to specific concentrations. For example, if a 20% by weight solution of AmSS is cured at 25°C for 14 days and the polymer content in the solution is at least 0.25% by weight or less, and further 0.1% by weight or less, it is determined that spontaneous polymerization of AmSS has been suppressed.
[0020] The polar organic solvent is not particularly limited as long as it dissolves AmSS at a high concentration and is not a poor solvent for oil-soluble vinyl monomers, but is an organic solvent whose Hansen solubility parameters (a) to (c) are within the following ranges. (a) Dispersion term δ d =16.5~18.5MPa 1 / 2 (b) Polarization term δ p =11.5~16.5MPa 1 / 2 (c) Hydrogen bond term δ h = 7.0~12.5MPa 1 / 2 The Hansen solubility parameter is an index developed mainly for evaluating the solubility of polymers (for example, Non-Patent Document 2), and in the present invention, the values described in the following Non-Patent Document 3 were used. Non-patent document 2: Hiroshi Yamamoto, Kagaku Kogyo, May 2010 issue, pages 66-73) Non-patent document 3: Charles M. Hansen, Hansen Solubility Parameters, A User's Handbook, 2 nd edition, CRC Press 2007, pp. 347-483)
[0021] Considering solubility, boiling point, toxicity, and availability, it is more preferable that the polar organic solvent contains at least one organic solvent selected from N-methyl-2-pyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and 1,3-dimethyl-2-imidazolidinone at 80% by weight or more. In addition, as long as it does not deviate from the range of the solubility parameter, a solvent (described later) to be added when copolymerizing an oil-soluble vinyl monomer may be added at this stage. For example, ethylene glycol, glycerin, triethanolamine, and the like have the second largest hydrogen bond term δ after water. h Although the effect is smaller than that of water, a solvent having the formula (I) may be added in a small amount since it has the effect of suppressing spontaneous polymerization of AmSS in a polar organic solvent.
[0022] The concentration of AmSS in the polar organic solvent solution is not particularly limited. However, when producing a film-like copolymer, for example, by coating a substrate with a monomer solution and polymerizing it, or by impregnating a support with a monomer solution and polymerizing it, a concentration as high as possible is preferred, and in consideration of solubility, a concentration of 20.0% by weight to 45.0% by weight is more preferred.
[0023] The appropriate amount or concentration of water used in the present invention varies depending on the amount of aliphatic amine added, but it is preferable that the water content be 300.0 mol % or less relative to AmSS (i.e., calculated by "100 x moles of water / moles of AmSS"). When no aliphatic amine is added, 100.0 mol% or more of AmSS is preferable. Although the mechanism is unclear, it is presumed that the aggregation state of AmSS molecules in a polar organic solvent is broken by 100 mol% or more of water relative to AmSS. The upper limit of the water content used should be such that the solubility parameter of the solvent described later does not deviate from the appropriate range when an AmSS copolymer is produced using a polar organic solvent solution of AmSS, and is preferably 250 mol% or less. The presence of a specific concentration of water can reduce the minimum concentration of polymerization inhibitor required to suppress spontaneous polymerization. Although the mechanism is unclear, spontaneous polymerization can be suppressed by adding an aliphatic amine even when the water content is less than 100.0 mol%. The appropriate amount of aliphatic amine varies depending on the water content, but is usually 20.0 mol% or less of AmSS (100 x moles of amine / moles of AmSS).
[0024] The amount or concentration of the organic polymerization inhibitor used in the present invention is 0.0020 (20×10) on a molar basis relative to AmSS. -4 ) mol% to 0.500 mol% (100 × moles of polymerization inhibitor / moles of AmSS), and taking into consideration adverse effects such as a decrease in polymerization rate, molecular weight, and copolymerizability in the copolymerization step, 0.375 mol% or less is more preferable, and 0.0020 (20 × 10 -4 ) mol % to 0.250 mol % is particularly preferable.
[0025] The polymerization inhibitor is not limited as long as it dissolves in the polar organic solvent used in the present invention and inhibits the polymerization of AmSS. Examples of the polymerization inhibitor that can be used include phenol-based polymerization inhibitors, phenothiazine, and stable nitroxyl radicals.
[0026] Examples of the phenol-based polymerization inhibitor include 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 2,4,6-tri-tert-butylphenol, 2,6-di-tert-butyl-4-ethylphenol, 4-sec-butyl-2,6-di-tert-butylphenol, 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 4-ethoxyphenol, 4-cyanophenol, 4-butoxyphenol, and 3-ethoxyphenol. phenol, 2,5-dimethoxyphenol, 2,6-dimethoxyphenol, 4-tert-butylcatechol, hydroquinone, methylhydroquinone, 2-methoxyhydroquinone, 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)mesitylene, 2,2',6,6'-tetra-tert-butyl-4,4'-dihydroxybiphenyl, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) N,N'-(Hexane-1,6-diyl)bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,6-Hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3,5-di-tert-butyl-4-hydroxybenzoate, N,N'-(Hexane-1,6-diyl)bis[3-(3,5 -di-tert-butyl-4-hydroxyphenyl)propanamide, bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propanoic acid][oxalyl bis(azanediyl)]bis(ethane-2,1-diyl), tris(3,5-tert-butyl-4-hydroxybenzyl)isocyanurate, diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, 2,2-thiodiethyl bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate Examples of stable nitroxyl radicals include 2,2,6,6-tetramethylpiperidine 1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, 4-(2-hydroxypropoxy-3-(2-hydroxyethoxy))-2,2,6,6-tetramethylpiperidin-1-ol, 4-(3-hydroxypropoxy-2-(2-hydroxyethoxy))-2,2,6,6-tetramethylpiperidin-1-ol, etc. In addition to the above, examples of bromine compounds that have a weak polymerization inhibitory effect on styrene sulfonate, such as lithium bromide, sodium bromide, and ammonium bromide, are listed.
[0027] Among these, 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 4-ethoxyphenol, 4-cyanophenol, 4-butoxyphenol, 3-ethoxyphenol, 2,5-dimethoxyphenol, 2,6-dimethoxyphenol, 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 4-tert-butylcatechol, hydroquinone, methylhydroquinone, 2-methoxyhydroquinone, 2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, which have relatively small molecular weights and are effective when added in small amounts, are more preferred.
[0028] The aliphatic amine is not particularly limited as long as it dissolves in the organic solvent solution of AmSS of the present invention, but in consideration of the amount to be added, an aliphatic amine having 8 or less carbon atoms is preferred, such as 2-hydroxyethylamine, diethylamine, diethanolamine, N-methylethanolamine, N-methyl-N,N-diethanolamine, piperidine, morpholine, N-methylpiperazine, triethylamine, triethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dimethylcyclohexylamine, N-methylpiperidine, N-methylmorpholine, 2-[(2-dimethylamino)ethoxy]ethanol, bis(2-dimethylaminoethyl)ether, monoisopropanolamine, diisopropanolamine, diethanolisopropanolamine, and 2-amino-2-methyl-1-propanol.
[0029] Next, a copolymerization method of AmSS and an oil-soluble vinyl monomer using a polar organic solvent solution of AmSS will be described. Since the solubility of monomers and polymers varies greatly depending on the composition, it is necessary to maintain their solubility in the polymerization process and to precisely control the solvent composition so as to prevent the copolymer from precipitating as much as possible. Therefore, when copolymerizing an oil-soluble vinyl monomer, a polymerization initiator, and, if necessary, a chain transfer agent (molecular weight regulator), etc., it is advisable to add another solvent and adjust the solvent composition so that it falls within the range of the Hansen solubility parameters (d) to (f) below. (d) Dispersion term δ d =17.5~18.5MPa 1 / 2 (e) Polarization term δ p =12.0~16.5MPa 1 / 2 (f) Hydrogen bond term δ h = 8.5~12.5MPa 1 / 2
[0030] For example, oil-soluble vinyl monomers such as AmSS and styrene are soluble in solvents such as N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and 1,3-dimethyl-2-imidazolidinone, but the respective homopolymers and copolymers are not necessarily soluble in these solvents, so that the polymers precipitate during polymerization and the desired copolymers cannot be obtained. As a result of intensive research by the present inventors, it was found that AmSS and oil-soluble vinyl monomers can be copolymerized in a wide range of compositions by optimizing the solvent composition so as to increase the lower limit of the Hansen solubility parameter of the solvent from the above solubility parameters (a) to (c) before polymerization.
[0031] This is thought to be because the solubility of the AmSS structural unit, which is more likely to aggregate in organic solvents, was increased by slightly increasing the lower limit of the Hansen solubility parameter. d , polarization term δ p , hydrogen bond term δ h are 18.6, 1.0, and 4.1 MPa, respectively. 1 / 2 , and the dispersion term of n-butyl methacrylate δ d , polarization term δ p , hydrogen bond term δ h are 15.6, 6.4, and 6.6 MPa, respectively. 1 / 2 and the dispersion term of polystyrene, δ d , polarization term δ p , hydrogen bond term δ h are 18.5, 4.5, and 2.9 MPa, respectively. 1 / 2 Compared with the above solubility parameters (a)-(c) and (d)-(f), the polarization term δ p , hydrogen bond term δ h is extremely small (it should be noted that the solubility parameters of AmSS and its copolymers are not described in the above Non-Patent Document 3). Therefore, these polarization terms δ p and hydrogen bond δ h If is too large, the copolymer will precipitate due to the aggregation of styrene structural units, so precise control of the solubility parameter is essential. Here, compounds whose structures change due to reactions, such as monomers, polymerization initiators, and chain transfer agents, are not considered as solvents and are not taken into account in the calculation of the solubility parameter.
[0032] The solvent for adjusting the solubility parameter is not particularly limited as long as it maintains the solubility of each monomer and polymer, and examples thereof include organic solvents such as ethylene glycol, propylene glycol, glycerin, methanol, acetone, acetonitrile, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, methoxyethanol, ethoxyethanol, 1-methoxy-2-propanol, propylene glycol monomethyl ether, dioxane, dihydrolevoglucosenone, dimethoxyethane, triethanolamine, and tetraethylene glycol, and water. Among these, ethylene glycol, propylene glycol, 1-propanol, 2-propanol, methoxyethanol, dihydrolevoglucosenone, dimethoxyethane, and water are more preferred, as they have a relatively high boiling point and can adjust the solubility parameter with a small amount.
[0033] Examples of solvents that satisfy the above solubility parameters include a 90 / 10 volume% N-methylpyrrolidone / water mixed solution, a 95 / 5 volume% N-methylpyrrolidone / water mixed solution, a 90 / 10 volume% N-methylpyrrolidone / ethylene glycol mixed solution, a 90 / 10 volume% N-methylpyrrolidone / triethanolamine mixed solution, a 90 / 10 volume% N-methylpyrrolidone / triethanolamine / water mixed solution, a 90 / 5 / 5 volume% N-methylpyrrolidone / ethylene glycol monomethyl ether mixed solution, a 50 / 50 volume% dimethylsulfoxide / N-methylpyrrolidone mixed solution, and a 80 / 20 volume% N-methylpyrrolidone / methanol mixed solution.
[0034] Examples of the oil-soluble vinyl monomer include styrenes such as styrene, chlorostyrene, dichlorostyrene, bromostyrene, dibromostyrene, fluorostyrene, trifluorostyrene, nitrostyrene, cyanostyrene, α-methylstyrene, p-chloromethylstyrene, p-cyanostyrene, p-acetoxystyrene, p-styrenesulfonyl chloride, ethyl p-styrenesulfonyl, methyl p-styrenesulfonyl, propyl p-styrenesulfonyl, p-butoxystyrene, 2-vinylpyridine, 4-vinylpyridine, 3-isopropenyl-α,α'-dimethylbenzyl isocyanate, and divinylbenzene; methyl acrylate; , ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, hexyl acrylate, decyl acrylate, lauryl acrylate, octyl acrylate, dodecyl acrylate, stearyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, bornyl acrylate, 2-ethoxyethyl acrylate, 2-butoxyethyl acrylate, 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, methoxyethylene glycol acrylate, ethyl carbitol acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 3-(trimethoxysilyl)propyl acrylate, polyethylene glycol acrylate, glycidyl acrylate, 2-(acryloyloxy)ethyl phosphate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,2-trifluoroethyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,4,4,4-Hexafluorobutyl, ethylene glycol diacrylate, triethylene glycol diacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate and other acrylic esters, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, sec-butyl methacrylate, i-butyl methacrylate, i-propyl methacrylate, decyl methacrylate, lauryl methacrylate, octyl methacrylate, dodecyl methacrylate, stearyl methacrylate, cyclohexyl methacrylate, bornyl methacrylate, benzyl methacrylate, phenyl methacrylate, glycidyl methacrylate, polyethylene glycol methacrylate, 2-hydroxyethyl methacrylate, tetrahydrofurfuryl methacrylate, methoxyethylene glycol methacrylate, ethyl carbitol ...tetrahydrofuryl methacrylate, methoxyethylene glycol methacrylate, ethyl carbitol methacrylate, 2-hydroxyethyl methacrylate, tetrahydrofurfuryl methacrylate, tetrahydrofuryl methacrylate propyloxypropyl, 4-hydroxybutyl methacrylate, 2-(methacryloyloxy)ethyl phosphate, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 3-(dimethylaminopropyl) methacrylate, 2-(isocyanato)ethyl methacrylate, 2,4,6-tribromophenyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, 2,2,3,4,4,Methacrylic acid esters such as 4-hexafluorobutyl, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, and polyethylene glycol dimethacrylate, N-cyclohexylmaleimide, N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, N-(chlorophenyl)maleimide, N-(methylphenyl)maleimide, N-(isopropylphenyl)maleimide, N-(sulfofuranyl)maleimide, N-phenyl)maleimide, N-methylphenylmaleimide, N-bromophenylmaleimide, N-naphthylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-(nitrophenyl)maleimide, N-benzylmaleimide, N-(4-acetoxy-1-naphthyl)maleimide, N-(4-oxy-1-naphthyl)maleimide, N-(3-fluoranthyl)maleimide, N-(5-fluoresceinyl)maleimide, N -(1-pyrenyl)maleimide, N-(2,3-xylyl)maleimide, N-(2,4-xylyl)maleimide, N-(2,6-xylyl)maleimide, N-(aminophenyl)maleimide, N-(tribromophenyl)maleimide, N-[4-(2-benzimidazolyl)phenyl]maleimide, N-(3 ,5-dinitrophenyl)maleimide, N-(9-acridinyl)maleimide, 4,4'-diphenylmethane bismaleimide, phenylene bismaleimide and other maleimides, dibutyl fumarate, dipropyl fumarate, diethyl fumarate, dicyclohexyl fumarate and other fumaric acid diesters, butyl fumarate, propyl fumarate, ethyl fumarate and other fumaric acid monoesters, dibutyl maleate, dipropyl maleate, diethyl maleate and other maleic acid diesters, butyl maleate, propyl maleate, ethyl maleate, dicyclohexyl maleate and other maleic acid monoesters, acrylonitrile, methacrylonitrile, fumaronitrile, vinyl chloride, N,N'-methylenebis(acrylamide), N,N'-methylenebis(methacrylamide), N,Examples of the monomers include N'-trimethylenebis[2-(vinylsulfonyl)acetamide] and N-vinylcarbazole. Among these, styrenes, methacrylic acid esters, acrylic acid esters, and maleimides are more preferable in consideration of copolymerizability with AmSS and availability. The molar ratio of the oil-soluble vinyl monomer to AmSS varies greatly depending on the application, but AmSS / oil-soluble vinyl monomer is 99 / 1 mol% to 1 / 99 mol%. If AmSS is less than 1 mol%, the copolymer cannot exhibit the characteristics of AmSS, and if the oil-soluble vinyl monomer is less than 1 mol%, the copolymer cannot exhibit the characteristics of the oil-soluble vinyl monomer.
[0035] The higher the monomer concentration during copolymerization, the more favorable it is in terms of polymerization rate, and in particular, when a copolymer membrane is produced by a method such as coating a substrate with a monomer solution or impregnating a support with a monomer solution and polymerizing it, the higher the monomer concentration is in terms of membrane performance (for example, JP 2016-033204 A, JP 7386705 A, and JP 2022-502522 A), and the total monomer concentration is usually 20.0% by weight or more. In addition, since the monomer solution of the present invention uses an organic solvent as the main solvent and has excellent wettability to organic materials such as plastics, it is also useful for surface modification of organic materials by graft polymerization (for example, Kyoichi Saito, Polymer Adsorbent Revolution by Graft Polymerization, pages 8 to 10, Maruzen Publishing, published in 2014). In the case of graft polymerization, if the monomer concentration is too high, there is a tendency for a free polymer that is not grafted to be generated, so the monomer concentration does not necessarily need to be high, and may be 5.0% by weight to 20.0% by weight.
[0036] The radical polymerization initiator used in the present invention is not particularly limited as long as it dissolves in the monomer solution. Examples of the radical polymerization initiator include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, benzoyl peroxide, dilauryl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)-cyclohexane, cyclohexanone peroxide, and t-butyl peroxide. peroxide compounds such as butyl peroxybenzoate, t-butyl peroxyisobutyrate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxyisopropyl carbonate, cumyl peroxyoctoate, hydrogen peroxide, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methyl) butyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis{2-methyl-N-[1,1'-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis{2-(2-imidazolin-2-yl)propane]dihydrochloride chloride, 2,2'-azobis{2-(2-imidazolin-2-yl)propane]disulfate dihydrate, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl)propane]}dihydrochloride, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane)dihydrochloride, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]tetrahydrate, 1,Azo compounds such as 1'-azobis(1-acetoxy-1-phenylmethane), 4,4'-diazenediylbis(4-cyanopentanoic acid), α-hydro-ω-hydroxypoly(oxyethylene) polycondensates, 4,4'-bis(diethylamino)benzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, ethyl-4-(dimethylamino)-benzoate, [4-(methylphenylthio)phenyl]-phenylmethane, ethylhexyl-4-dimethylamino Benzoate, benzophenone, methyl-o-benzoylbenzoate, o-benzoylbenzoic acid, 4-methylbenzophenone, 1-hydroxycyclohexyl phenyl ketone, methylbenzoyl formate, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate, 2,2-dimethoxy-2-phenyl acetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propane, and lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate are examples of photopolymerization initiators. From the viewpoint of economy, when using the above-mentioned peroxide-based polymerization initiator, a reducing agent such as ascorbic acid, erythorbic acid, aniline, or a tertiary amine can be used in combination, if necessary. The amount of the radical polymerization initiator used is usually 0.01 mol % to 10 mol % based on the total monomers, and taking into consideration the purity of the target product, it is more preferably 0.01 mol % to 2 mol %.
[0037] The molecular weight regulator (chain transfer agent) is not particularly limited as long as it is soluble in the monomer solution, and examples thereof include thioglycolic acid, thiomalic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiosalicylic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, thiomalonic acid, dithiosuccinic acid, thiomaleic acid, thiomaleic anhydride, dithiomaleic acid, thioglutaric acid, cysteine, homocysteine, 5-mercaptotetrazoleacetic acid, 3-mercapto-1-propanesulfonic acid, 3-mercaptopropane-1,2-diol, mercaptoethanol, 1 ,2-dimethylmercaptoethane, 2-mercaptoethylamine hydrochloride, 6-mercapto-1-hexanol, 2-mercapto-1-imidazole, 3-mercapto-1,2,4-triazole, cysteine, N-acylcysteine, glutathione, N-butylaminoethanethiol, N,N-diethylaminoethanethiol and other mercaptans, diisopropyl xanthogen disulfide, diethyl xanthogen disulfide, diethylthiuram disulfide, 2,2'-dithiodipropionic acid, 3,3'-dithiodipropionic acid, 4,4'-dithiodibutanoic acid, 2,2'-dithiobisbenzoic acid and other disulfides, iodoform and other halogenated hydrocarbons, benzyl dithiobenzoate, 2-cyanoprop-2-yl dithiobenzoate, 4- Examples of the thiocarbonylthio compounds include cyano-4-(thiobenzoylthio)pentanoic acid, 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, S,S-dibenzyltrithiocarbonate, 3-((((1-carboxyethyl)thio)carbonothioyl)thio)propanoic acid, and cyanomethyl(3,5-dimethyl-1H-pyrazole)carbodithioate; iodide alkyl compounds such as α-iodobenzyl cyanide, 1-iodoethylbenzene, ethyl 2-iodo-2-phenylacetate, 2-iodo-2-phenylacetic acid, 2-iodopropanoic acid, and 2-iodoacetic acid; diphenylethylene, p-chlorodiphenylethylene, p-cyanodiphenylethylene, α-methylstyrene dimer, organic tellurium compounds, and sulfur.Among these, when it is desired to narrow the molecular weight distribution by living radical polymerization, thiocarbonylthio compounds and alkyl iodide compounds are preferred as chain transfer agents from the viewpoint of controllability. The molecular weight regulator can be used to lower the molecular weight of the copolymer, and can also be used to suppress a rapid and non-uniform polymerization reaction and to suppress non-uniformity in the composition and crosslinking structure of the resulting polymer.
[0038] In the present invention, the polymerization temperature is preferably equal to or lower than the boiling point of the solvent, and although it varies depending on the solvent composition, it is 10° C. to 200° C., more preferably 40° C. to 150° C., and taking into consideration the polymerization conversion rate and the volatilization of the oil-soluble vinyl monomer, it is 60° C. to 100° C. The polymerization time is preferably 0.5 hours to 30 hours, and more preferably 1 hour to 20 hours.
[0039] The molecular weight of the AmSS copolymer obtained in the present invention varies depending on the application, but is usually 1,000 to 2,000,000 daltons in number average molecular weight. In the case of crosslinked products such as cation exchange membranes, it is difficult to measure the molecular weight. EXAMPLES
[0040] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples in any way.
[0041] <Medicines used> NaSS: Sodium styrenesulfonate (Tosoh Finechem Corporation, purity 88.2%, sodium bromide 2.2% by weight, sodium hydroxide 0.40% by weight, sodium sulfate 0.50% by weight, water 7.2% by weight, polymer content 0.01% by weight, nitrite content 70 ppm) LiSS: Lithium styrenesulfonate (Tosoh Finechem Corporation, purity 85.3%, lithium bromide 2.5% by weight, lithium hydroxide 0.45% by weight, lithium sulfate 0.50% by weight, water 7.1% by weight, polymer content 0.04% by weight, nitrite content 60 ppm) Ammonium sulfate: Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent MEPE: 4-Methoxyphenol (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent) HQ: Hydroquinone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) MEHQ: Methylhydroquinone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) TBC: 4-tert-butylcatechol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) BHT: 2,6-di-tert-butyl-p-cresol (Kawaguchi Chemical Industry Co., Ltd.) LiNO2: Lithium nitrite (Honjo Chemical Co., Ltd., 40% by weight aqueous solution) LiBr: Anhydrous lithium bromide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) NMP: N-methylpyrrolidone (manufactured by Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, moisture content 10 ppm or less) DMSO: Dimethyl sulfoxide (Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, moisture content 10 ppm or less) DMI: 1,3-Dimethyl-2-imidazolidinone (Kanto Chemical Co., Ltd., dehydrated grade, moisture content 50 ppm or less) EG: Ethylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, moisture content 10 ppm or less) MEK: Methyl ethyl ketone (manufactured by Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, moisture content 10 ppm or less) THF: Tetrahydrofuran (manufactured by Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, water content 30 ppm or less) ACN: Acetonitrile (manufactured by Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, water content 10 ppm or less) 1PA: 1-propanol (manufactured by Fujifilm Wako Pure Chemical Industries, ultra-dehydrated grade, moisture content 10 ppm or less) 2-Dimethylaminoethanol (FUJIFILM Wako Pure Chemical Industries, Ltd., special grade, purity ≧99.0%) N,N-Dimethylcyclohexylamine (FUJIFILM Wako Pure Chemical Industries, Ltd., special grade, purity ≧98.0%) N-Methylmorpholine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., special grade, purity ≧99.0%) AIBN: 2,2'-Azobis(isobutyronitrile) (manufactured by Fujifilm Wako Pure Chemical Corporation)
[0042] <Quantification of moisture in AmSS> Measurement was carried out using an infrared moisture meter under the following conditions. Apparatus: FD-720 manufactured by Kett Science Laboratory Co., Ltd. Conditions: Approximately 5 g of the sample was collected and heated at 120 °C for 20 minutes.
[0043] <Purity analysis of AmSS by redox titration> The active double bonds were quantified by the following redox titration method to obtain the AmSS purity (i.e., including ortho and meta isomers in addition to the para isomer). (1) Instruments and apparatus 1) Weighing bottle: diameter 50 mm, depth 70 mm 2) 500 ml and 1000 ml volumetric flasks 3) 500 ml conical flask with stopper 3) Electronic chemical balance (2) Reagents 1) Bromine solution: 22.00 g of potassium bromide (KBr) and 3.00 g of potassium bromate (KBrO3) were dissolved in pure water to make a total volume of 1000 ml. 2) Sulfuric acid aqueous solution (concentrated sulfuric acid / pure water volume ratio = 1 / 1) 3) Potassium iodide aqueous solution (200 g / L) 4) 0.1 mol / L sodium thiosulfate aqueous solution 5) Starch aqueous solution: 6.00 g of starch was dissolved in pure water to make a total volume of 1000 ml. (3) Procedures 1) Weigh 20 g of the sample into a weighing bottle to the nearest 0.1 mg. 2) Transfer it to a 500 ml volumetric flask with pure water and make the liquid volume approximately 400 ml. 3) Add a magnetic rotor and stir to dissolve the sample. 4) Remove the rotor, adjust the liquid level to the mark with pure water and shake well to obtain the test solution. 5) Add 25 ml of the bromine solution to a 500 ml conical flask with stopper containing 200 ml of pure water. 6) After adding 5 ml of the test solution, add 10 ml of the sulfuric acid aqueous solution, seal tightly, and let stand for 20 minutes. 7) Quickly add 10 ml of the potassium iodide aqueous solution and let stand for 10 minutes. 8) Titrate with the sodium thiosulfate aqueous solution. After the yellow color of the solution fades, add 1 ml of the starch solution as an indicator and titrate until the blue color of the iodine starch disappears. 9) Separately, as a blank test, add 200 ml of pure water to an Erlenmeyer flask with a stopper, add 25 ml of the bromine solution, quickly add 10 ml of the potassium iodide aqueous solution and 10 ml of the sulfuric acid aqueous solution, and perform the operation in 8). (4) Calculation Calculate the AmSS content according to the following formula. A = 100×[0.01006×(a - b)×f] / (S×5 / 500) A: AmSS content (%) a: Volume of the sodium thiosulfate aqueous solution required for the blank test (ml) b: Volume of the sodium thiosulfate aqueous solution required for this test (ml) f: Normality of the sodium thiosulfate aqueous solution S: Sample amount (g)
[0044] <Elemental Analysis of AmSS and Copolymer> The carbon, hydrogen, and nitrogen contents were quantified using an elemental analyzer. Apparatus: PerkinElmer 2400II
[0045] <Quantification of Sulfur Content in AmSS and Copolymer> The combustion gas of AmSS or copolymer burned by the oxygen flask combustion method was absorbed by the hydrogen peroxide absorption solution to prepare the absorption solution. Next, the sulfate ion concentration in the absorption solution was quantified by ion chromatography (see the following items for measurement conditions) and converted to sulfur content.
[0046] <Quantification of Bromine, Chlorine, Sulfuric Acid, and Nitrite Anions in AmSS> Quantification was performed using ion chromatography under the following conditions. Apparatus: IC - 2010 manufactured by Tosoh Corporation Column: TSKgel® guard column Super IC-AHS (4.6 mm I.D. × 1 cm) + TSKgel® SuperIC-Anion HS (4.6 mm I.D. × 10 cm) Column temperature: 40 °C, Injection volume: 30 μl, Flow rate: 1.5 ml / min Eluent: Carbonate buffer (7.5 mM - NaHCO3 + 0.8 mM - Na2CO3) Preparation of sample solution: The AmSS composition was dissolved in ultrapure water and diluted 10-fold, and then passed through a pretreatment cartridge (TOYOPAK® ODSM) to obtain a measurement sample. Calibration curve: Absolute calibration curve method using a standard solution
[0047] <Analysis of alkali metal content in AmSS> Using an inductively coupled plasma optical emission spectrometer OPTIMA 8300 (manufactured by PerkinElmer), the sodium and lithium contents were quantified (hereinafter abbreviated as ICP-AES). The target sample was wet-decomposed with sulfuric acid and nitric acid, and the decomposed sample was heated to dryness. Nitric acid was added to the dried sample, heated and dissolved, and after making a fixed volume of a predetermined amount, 1 ppm of scandium was added as an internal standard and quantified.
[0048] <Analysis of AmSS by proton nuclear magnetic resonance ( 1 1H-NMR)> Under the following conditions, the molar ratio of ammonium cations to styrene sulfonic acid units in AmSS was analyzed. (1) Preparation of sample The sample was dissolved in about 0.7 mL of dimethyl sulfoxide-d6 (99.5 wt%) containing about 0.05 wt% of tetramethylsilane as an internal standard substance to prepare a measurement sample. (2) Measuring instrument and conditions Model = AV-400M manufactured by Bruker Number of integrations = 16 Nuclide = 1H (3) Calculation of molar ratio of ammonium cation (NH4) / styrene sulfonic acid unit (SS) Calculated by the following formula. NH4 / SS = 〔n / (nH)〕 / 〔s / (sH)〕 s: Integral value of the peak derived from the vinyl group of SS (peak position: δ5.30 ppm, d) n: Integral value of the peak derived from NH4 (peak position: δ7.22 ppm, s, but may split into three depending on moisture) sH: Number of hydrogens of the peak of s (= 1) nH: Number of hydrogens of the peak of n (= 4) Note that the peak position is when dimethyl sulfoxide-d6 is used as the heavy solvent, and the chemical shift may vary slightly depending on the amount of impurities.
[0049] <Analysis of Polymer Content and Polymerization Inhibitor in AmSS Solution> Using gel permeation chromatography (GPC), analysis was performed under the following conditions. Apparatus: HLC-8320 manufactured by Tosoh Corporation Column: TSKgel (registered trademark) guard column AW-H / TSKgel (registered trademark) AW-6000 / TSKgel (registered trademark) AW-3000 / TSKgel (registered trademark) AW-2500 Eluent: 0.05 M sodium sulfate aqueous solution / acetonitrile = 65 / 35 (volume ratio) solution Sample: The AmSS solution was dissolved in the above eluent (about 1% by weight in terms of pure content) to obtain a sample solution. Flow rate, injection volume, column temperature: 0.6 ml / min, injection volume: 10 μl, column temperature: 40 °C Detector: UV detector (wavelength 230 nm) Calibration curve: Using sodium polystyrene sulfonate (3K manufactured by Sowa Kagaku) and the above eluent, standard solutions with different concentrations of sodium polystyrene sulfonate were prepared to create a calibration curve. Note that all absorption peaks with an elution time of less than 13.00 minutes were regarded as polymer content. Also, a calibration curve for the polymerization inhibitor was created in the same manner.
[0050] <Measurement of Polymerization Conversion Rate and Molecular Weight of Copolymerization of AmSS and Oil-Soluble Vinyl Monomer> Measured by GPC under the same conditions as above (however, the sample concentration was approximately 0.1% by weight in terms of monomer pure content). Incidentally, the molecular weight was calculated by creating a calibration curve from the peak top molecular weights and elution times of standard sodium polystyrene sulfonate (manufactured by Sowa Kagaku, 3K, 15K, 41K, 300K, 1000K, 2350K, 5000K) and automatically calculating it using in-house software. The polymerization conversion rate was calculated from the peak areas derived from each monomer before polymerization and the peak areas derived from the monomer after polymerization.
[0051] <Analysis of AmSS copolymer by infrared absorption spectroscopy (FT-IR)> Apparatus: Spectrum2000 manufactured by PerkinElmer Samples were prepared by the KBr tablet method and measured using a PerkinElmer System 2000. The measurement wavelength range was 4000 - 400 cm-1, and the number of measurements was 16 times.
[0052] <Measurement of solubility of AmSS> Solvent and an excess amount of AmSS were taken into a 50 ml glass standard bottle, sealed, and then dissolved while stirring at 25°C for 15 minutes using a magnetic stirrer. After that, it was left standing at 25°C for 30 minutes, and then the supernatant was collected with a syringe equipped with a membrane filter [DISMIC (registered trademark) 13HP045AN manufactured by Advantec Toyo Co., Ltd.], diluted with the above GPC eluent, and the concentration of AmSS in the supernatant was calculated by GPC measurement. The measurement conditions were the same as above, and standard solutions with different AmSS concentrations were prepared to create a calibration curve.
[0053] Synthesis Example 1 (Preparation of AmSS) 290.00 g (1.24 mol) of NaSS powder, 1.50 g (1.97 mol% with respect to NaSS) of 4-methoxyphenol, 160.00 g (1.21 mol) of ammonium sulfate, and 550.00 g of ion-exchanged water were charged into a cylindrical 2 L glass separable flask equipped with a reflux condenser, and a cation exchange reaction was carried out while stirring at an internal temperature of 45°C for 60 minutes using a stirrer (total solid content 43.00% by weight). Then, it was cooled to 30°C over 5 hours and aged for 2 hours as it was to obtain a white slurry liquid. The slurry was then centrifuged (600G x 20 minutes, room temperature) to obtain 212.40 g of plate-like wet crystals. The slurry had good drainage properties, and the moisture content of the wet crystals was 7.80% by weight as determined by an infrared moisture meter. The wet crystals were dried using a rotary evaporator at 45° C. for 60 minutes (pressure 660 Pa) to obtain 188.40 g of dry crystals. The sodium content determined by ICP of AmSS was 0.35 wt%, the nitrogen content determined by elemental analysis was 6.8 wt% and 1 The molar ratio of ammonium cations to styrenesulfonic acid units determined by H-NMR was 1.00, and therefore the dried crystals were determined to be the target product, AmSS. The moisture content of the above dried AmSS was 0.12% by weight, the 4-methoxyphenol content was 34 ppm, and the AmSS content, i.e., the vinyl purity, was 98.2% by weight (the yield based on the molar content of the raw material NaSS was 75%).
[0054] Synthesis Example 2 (Preparation of AmSS) The reaction was carried out under the same conditions as in Synthesis Example 1, except that 4-methoxyphenol was not added, and 215.30 g of plate-like wet crystals were obtained. The slurry had good drainage properties, and the moisture content of the wet crystals measured with an infrared moisture meter was 7.95% by weight. The wet crystals were dried using a rotary evaporator at 30° C. for 120 minutes (pressure 660 Pa) to obtain 189.20 g of dry crystals. The sodium content determined by ICP of AmSS was 0.35 wt%, the nitrogen content determined by elemental analysis was 6.8 wt% and 1 The molar ratio of ammonium cations to styrenesulfonic acid units determined by H-NMR was 1.00, and therefore the dried crystals were determined to be the target product, AmSS. The moisture content of the above dried AmSS was 0.23% by weight, and the AmSS content, i.e., the vinyl purity, was 98.0% by weight (the yield based on the molar content of the raw material NaSS was 76%).
[0055] Reference Example 1 (Stability of AmSS in aqueous solution) The dried AmSS (4.0042 g) prepared in Synthesis Example 1 and ion-exchanged water (12.4002 g) were placed in a 50 ml glass sample bottle, sealed with a resin cap, dissolved while stirring with a magnetic stirrer, and then aged (left to stand) at 25° C. The polymer content was quantified by periodically sampling and measuring by GPC. As a result, as shown in Table 1, the polymer content in the solution after 14 days of curing was 0.04 wt%, and the ratio of the number of moles of 4-methoxyphenol to the number of moles of AmSS in the solution was 56 × 10 -4 Despite the low molar concentration, it was confirmed to be stable in aqueous solution.
[0056] Comparative Example 1 (Stability of AmSS in DMSO solution) As in Reference Example 1, dried AmSS, dimethyl sulfoxide, and 40 wt% lithium nitrite aqueous solution were collected in a 50 ml glass sample bottle with the composition shown in Table 1, sealed with a resin cap, stirred with a magnetic stirrer to dissolve, and aged (left to stand) at 25° C. Periodically sampled and subjected to GPC measurement to quantify the polymer content. As a result, despite the presence of a high concentration of lithium nitrite, the polymer content in the solution was 1.75% by weight after 3 days of curing, exceeding 1% by weight (see FIG. 1), as shown in Table 1. In other words, it is clear that AmSS is highly susceptible to spontaneous polymerization in dimethyl sulfoxide, and that spontaneous polymerization cannot be suppressed by a high concentration of nitrous acid exceeding 9000 mol % or a low concentration of 4-methoxyphenol less than 100 mol %. The solubility parameters shown in Table 1 are calculated values from the polar organic solvent and the water present in the system (water in the super-dehydrated organic solvent was ignored).
[0057] Comparative Example 2 (Stability of AmSS in DMSO solution) Water was further added to Comparative Example 1, and the stability was evaluated under the same conditions as Comparative Example 1. As a result, the spontaneous polymerization property was slightly decreased by adding water, but the polymer content in the solution exceeded 3% by weight after 7 days of aging. In other words, it is clear that AmSS is highly susceptible to spontaneous polymerization in dimethyl sulfoxide, and spontaneous polymerization cannot be suppressed by high concentration nitrous acid exceeding 9000 mol%, water exceeding 100 mol%, or low concentration 4-methoxyphenol less than 100 mol%.
[0058] [Table 1]
[0059] Comparative Example 3 (Stability of AmSS in DMSO solution) As in Comparative Examples 1 and 2, dried AmSS, dimethyl sulfoxide, 4-methoxyphenol, and ion-exchanged water were collected in a 50 ml glass sample bottle in the composition shown in Table 2, sealed with a resin cap, dissolved with a magnetic stirrer, and aged (left to stand) at 25° C. The polymer content was quantified by periodically sampling and measuring by GPC. As a result, as shown in Table 2, when the amount of 4-methoxyphenol relative to AmSS in the solution was less than 100 mol%, spontaneous polymerization could not be suppressed even when the amount of water relative to AmSS was 100 mol% or more, and the polymer content exceeded 6 wt% after 7 days of curing.
[0060] Comparative Example 4 (Stability of AmSS in DMSO solution) The stability of AmSS was evaluated under all the same conditions as in Comparative Example 3, except for changing the composition to that shown in Table 2. As a result, even if 100 mol % or more of 4-methoxyphenol was present relative to AmSS in the solution, spontaneous polymerization could not be sufficiently suppressed when the moisture relative to AmSS was 100 mol % or less, and the polymer content exceeded 7 wt % after aging for 7 days.
[0061] Comparative Examples 5-6 (Stability of AmSS in DMSO Solution) The stability of AmSS was evaluated under the same conditions as in Comparative Example 3, except for changing the composition to that shown in Table 2. As a result, even if the moisture content of AmSS in the solution was 100 ppm or less, spontaneous polymerization could be suppressed by increasing the amount of 4-methoxyphenol to 5000 mol % or more relative to AmSS. However, as shown in Comparative Examples 10 to 11, as a result of copolymerization with styrene, the polymerization conversion rate and the number average molecular weight of the produced polymer decreased compared to Examples 10 to 13 (Table 5). This is because an excess amount of 4-methoxyphenol inhibited the copolymerization of AmSS and styrene.
[0062] Comparative Example 7 (Stability of AmSS in NMP Solution) The stability of AmSS was evaluated in the same manner as in Comparative Examples 3 to 6, except that the composition was changed to that shown in Table 2. As a result, as shown in Table 2, when the amount of 4-methoxyphenol and water relative to the amount of AmSS in the solution was less than 100 mol %, spontaneous polymerization could not be sufficiently suppressed. Furthermore, the solubility of ammonium polystyrene sulfonate in N-methylpyrrolidone was poor, and the polymer precipitated at least after aging for 7 days.
[0063] Comparative Example 8 (Stability of AmSS in NMP Solution) The stability of AmSS was evaluated in the same manner as in Comparative Examples 3 to 6, except for changing the composition to that shown in Table 2. As a result, as shown in Table 2, even if 100 mol % or more of 4-methoxyphenol was present relative to AmSS in the solution, spontaneous polymerization could not be sufficiently suppressed when the water content relative to AmSS was less than 100 mol %. Furthermore, the solubility of ammonium polystyrene sulfonate in N-methylpyrrolidone was poor, and polymers precipitated at least after aging for 7 days.
[0064] Comparative Example 9 (Stability of AmSS in NMP Solution) The stability of AmSS was evaluated in the same manner as in Comparative Examples 3 to 6, except for the composition shown in Table 2. As a result, as shown in Table 2, even if the water content of AmSS in the solution was 100 ppm or more, spontaneous polymerization could not be sufficiently suppressed when 4-methoxyphenol was less than 100 mol% relative to AmSS. Furthermore, the solubility of ammonium polystyrene sulfonate in N-methylpyrrolidone was poor, and polymers precipitated at least after aging for 7 days.
[0065] [Table 2]
[0066] Example 1 (Stability of AmSS in DMSO solution) The spontaneous polymerization of the AmSS solution was evaluated under the same conditions as Comparative Examples 3 to 6, except for changing the composition to that shown in Table 3. As a result, as shown in Table 3, when 100 ppm or more of 4-methoxyphenol and 100 mol % or more of water were present relative to the AmSS in the solution, the polymer content was as low as 0.21 wt % even after aging for 14 days, which clearly shows that spontaneous polymerization was significantly suppressed compared to Comparative Examples 3 to 6 (FIGS. 1 and 2).
[0067] Example 2 (Stability of AmSS in DMSO solution) Except for changing the composition to that shown in Table 3, the spontaneous polymerization of the AmSS solution was evaluated under the same conditions as in Comparative Examples 3 to 6. As a result, as shown in Table 3, even if the moisture content is further reduced to 2.18% by weight compared to 4.68% by weight in Example 1, by increasing the amount of 4-methoxyphenol from 25 ppm to 139 ppm, the polymer content is still as low as 0.06% by weight even after 14 days of curing, which clearly shows that the polymer content can be further suppressed.
[0068] Example 3 (Stability of AmSS in NMP solution) The solvent was changed to N-methylpyrrolidone, and the spontaneous polymerization property of the AmSS solution was evaluated with the composition shown in Table 3. The evaluation conditions other than the composition were all the same as in Examples 1 and 2. As a result, as shown in Table 3, when 100 mol % or more of 4-methoxyphenol and 100 mol % or more of water were present relative to AmSS in the solution, the polymer content was 0.02 wt %, less than 1 wt %, even after 14 days of curing, and it is clear that spontaneous polymerization was significantly suppressed compared to Comparative Examples 7 to 9.
[0069] Example 4 (Stability of AmSS in NMP solution) The solvent was changed to N-methylpyrrolidone, and the spontaneous polymerization property of the AmSS solution was evaluated with the composition shown in Table 3. The evaluation conditions other than the composition were all the same as in Examples 1 and 2. As a result, as shown in Table 3, since the amounts of 4-methoxyphenol and water were both reduced compared to Example 3, the amount of polymer produced increased slightly to 0.04 wt %, but it is clear that spontaneous polymerization was significantly suppressed compared to Comparative Examples 7 to 9.
[0070] Example 5 (Stability of AmSS in NMP solution) The solvent was changed to N-methylpyrrolidone, and the spontaneous polymerization property of the AmSS solution was evaluated with the composition shown in Table 3. The evaluation conditions other than the composition were all the same as in Examples 1 and 2. As a result, as shown in Table 3, since the amounts of 4-methoxyphenol and water were both increased compared to Example 3, the amount of polymer produced was reduced to 0.01 wt %, and it is clear that spontaneous polymerization was significantly suppressed compared to Comparative Examples 7 to 9.
[0071] [Table 3]
[0072] Examples 6 to 8 (Stability of AmSS in DMSO solution) The type of organic polymerization inhibitor was changed, and the spontaneous polymerization of the AmSS solution was evaluated under the same conditions as in Examples 1 and 2. As a result, as shown in Table 4, when 100 mol % or more of an organic polymerization inhibitor and 100 mol % or more of water were present relative to AmSS in the solution, the polymer content was less than 1 wt % even after 14 days of curing, and it is clear that spontaneous polymerization was significantly suppressed compared to Comparative Examples 3 to 6.
[0073] Example 9 (Stability of AmSS in DMSO solution) The spontaneous polymerization of the AmSS solution was evaluated under the same conditions as in Examples 1 and 2, while changing the type of organic polymerization inhibitor and the monomer concentration. As a result, as shown in Table 4, although the amount of organic polymerization inhibitor was increased compared to Example 7, the amount of polymer produced increased slightly due to the reduction in water content, but it is clear that spontaneous polymerization was significantly suppressed compared to Comparative Examples 3 to 6.
[0074] [Table 4]
[0075] Example 10 In a 50 ml three-neck glass flask equipped with a cooling condenser and a nitrogen inlet tube, fresh AmSS solution prepared in Example 1, styrene, AIBN (10 wt % N-methylpyrrolidone solution), and dimethyl sulfoxide were collected in the composition shown in Table 5, and deoxygenated by repeatedly reducing the pressure with an aspirator and introducing nitrogen. The flask was then immersed in an oil bath at 70°C, and polymerization was carried out for 24 hours under a nitrogen atmosphere while stirring with a magnetic induction stirrer. The polymerization solution was collected at predetermined intervals to check the polymerization conversion rate. As a result, both AmSS and styrene were polymerized at a high conversion rate of 90% or more, and a polymer with a number average molecular weight of 66,400 was produced. Figure 3 shows the relationship between the polymerization time and the polymerization conversion rate of AmSS and styrene. AmSS and styrene were consumed at almost the same rate, and no polymer precipitation (polystyrene is insoluble in dimethyl sulfoxide) was observed, so it was determined that the copolymerization proceeded smoothly. That is, it is considered that there is no adverse effect on copolymerization when the amount of 4-methoxyphenol relative to AmSS is 180 mol %.
[0076] Example 11 Copolymerization with styrene was carried out under the same conditions as in Example 10, except that the fresh AmSS solution prepared in Example 3 was used (Table 5). As a result, it was confirmed that even if the amount of 4-methoxyphenol contained in the AmSS solution increased to 963 mol% relative to AmSS, it had almost no adverse effect on the copolymerizability with styrene.
[0077] Example 12 Copolymerization with styrene was carried out under the same conditions as in Example 10, except that the fresh AmSS solution prepared in Example 9 was used (Table 5). As a result, since the polymerization inhibitor concentration was higher than in Examples 10 to 11, the polymerization conversion rate and molecular weight of AmSS and styrene were slightly lower, but it is clear that they were sufficiently higher than those of Comparative Examples 10 and 11.
[0078] Example 13 Copolymerization with styrene was carried out under the same conditions as in Example 10, except that the fresh AmSS solution prepared in Comparative Example 3 was used (Table 5). The content of 4-methoxyphenol in the AmSS solution was 56×10 -4 Since the amount was only mol %, the storage stability was poor as shown in Comparative Example 3. On the other hand, it was advantageous to produce a copolymer by adding a polymerization initiator, and the polymerization conversion rates of AmSS and styrene were equal to or higher than those of Examples 10 to 12.
[0079] Comparative Examples 10 to 11 Copolymerization with styrene was carried out under the same conditions as in Example 10, except that fresh AmSS solutions prepared in Comparative Examples 5 and 6 were used (Table 5). As a result, the polymerization conversion rate and the number average molecular weight of the produced polymer were lower than those in Examples 10 to 13 (Table 5). This is because an excess amount of 4-methoxyphenol inhibited the copolymerization of AmSS and styrene.
[0080] [Table 5]
[0081] Example 14 In a 50 ml three-neck glass flask equipped with a cooling condenser, a nitrogen inlet tube, and a magnetic induction type stirrer, the N-methylpyrrolidone solution of AmSS prepared in Example 5, styrene, AIBN (1 wt% N-methylpyrrolidone solution), and water as an additional solvent for adjusting the solubility parameter were collected in the composition shown in Table 6, and deoxygenated by repeatedly reducing the pressure with an aspirator and introducing nitrogen. Then, the flask was immersed in an oil bath at 70°C, and polymerization was carried out under a nitrogen atmosphere for 24 hours while stirring. As a result, the polymerization conversion rates of AmSS and styrene were 94% and 89%, respectively, and no polymer precipitation was observed throughout the experiment. Since the polymer showed a monomodal molecular weight distribution (Figure 4), it was determined that the copolymerization proceeded smoothly. This was because the solubility parameter of the polymerization solvent was optimized, making AmSS, the oil-soluble vinyl monomer styrene, and the copolymer all soluble in the polymerization solvent. Incidentally, polystyrene does not dissolve in the polymerization solvent. The solubility parameters shown in Table 6 are calculated values based on the amount of each solvent contained in the system. For example, the solubility parameter δ when the same volume of N-methylpyrrolidone and water are mixed is d is 0.5×18.0+0.5×15.5=16.75MPa 1 / 2 δ p , δ h is calculated in the same way.
[0082] [Table 6]
[0083] Example 15 Copolymerization of AmSS and styrene was carried out under the same conditions as in Example 14, except that the amounts of water and styrene as additional solvents were changed. As a result, the polymerization conversion rates of AmSS and styrene were 70% and 66%, respectively, and no polymer precipitation was observed throughout the process. Since the polymer showed a monomodal molecular weight distribution (Figure 5), it was determined that the copolymerization proceeded smoothly. This was because the solubility parameter of the polymerization solvent was optimized, making AmSS, the oil-soluble monomer styrene, and the copolymer all soluble in the polymerization solvent. Although the conversion rate was low, it can be improved by changing the type and amount of initiator, and the polymerization temperature, and it is believed to be fully practical.
[0084] Example 16 Copolymerization of AmSS and styrene was carried out under the same conditions as in Example 14, except that the amount of water as the additional solvent was reduced and the composition was changed to that shown in Table 6. As a result, the polymerization conversion rates of AmSS and styrene were 91% and 84%, respectively, and no polymer precipitation was observed throughout the experiment. Since the polymer showed a monomodal molecular weight distribution, it was determined that the copolymerization proceeded smoothly. This was because the solubility parameter of the polymerization solvent was optimized, making AmSS, the oil-soluble monomer styrene, and the copolymer all soluble in the polymerization solvent.
[0085] Example 17 In Example 14, the additional solvent for adjusting the solubility parameter of the polymerization solvent was changed to ethylene glycol, and the composition was changed to that shown in Table 6. Except for this, copolymerization of AmSS and styrene was carried out under the same conditions as in Example 14. As a result, the polymerization conversion rates of AmSS and styrene were 90% and 84%, respectively, and no polymer precipitation was observed throughout the experiment. Since the polymer showed a monomodal molecular weight distribution, it was determined that the copolymerization proceeded smoothly. This was because the solubility parameter of the polymerization solvent was optimized, making AmSS, the oil-soluble monomer styrene, and the copolymer all soluble in the polymerization solvent.
[0086] Example 18 In Example 15, the additional solvent for adjusting the solubility parameter of the polymerization solvent was changed to ethylene glycol, and the composition was changed to that shown in Table 6. The copolymerization of AmSS and styrene was carried out under the same conditions as in Example 15. As a result, the polymerization conversion rates of AmSS and styrene were 77% and 52%, respectively, and no polymer precipitation was observed. Since the polymer showed a monomodal molecular weight distribution, it was determined that the copolymerization proceeded smoothly. This is because the solubility parameter of the polymerization solvent was optimized, optimizing the solvent composition, making AmSS, the oil-soluble monomer styrene, and the copolymer all soluble in the polymerization solvent.
[0087] Comparative Example 12 Copolymerization of AmSS and styrene was carried out under the same conditions as in Example 14, except that no additional solvent was added to adjust the solubility parameter of the polymerization solvent. As a result, a large amount of polymer precipitated 3 hours after the start of polymerization because the solubility parameter δh was too low.
[0088] Comparative Example 13 Copolymerization of AmSS and styrene was carried out under the same conditions as in Example 15, except that no additional solvent was added to adjust the solubility parameter of the polymerization solvent. As a result, a large amount of polymer precipitated 3 hours after the start of polymerization because the solubility parameter δh was too low.
[0089] Reference examples 2~9 The solubilities (25° C.) of AmSS prepared in Synthesis Example 1 in various polar organic solvents were measured and are shown in Table 7. As is clear from Table 7, when the Hansen solubility parameters (a) to (c) of the polar organic solvent deviate from the following ranges, the solubility drops dramatically. If an organic polymerization inhibitor is added, it is expected that there will be no problem with storage stability, but the solubility is low, so there is little practical value. (a) Dispersion term δ d =16.5~18.5MPa 1 / 2 (b) Polarization term δ p =11.5~16.5MPa 1 / 2 (c) Hydrogen bond term δ h = 7.0~12.5MPa 1 / 2 When calculating the above solubility parameters, the water content of the organic solvent (ultra-dehydrated grade) was ignored, and only the water content of AmSS was considered as the solvent.
[0090] [Table 7]
[0091] Example 19 (Stability of AmSS in DMSO) Dry AmSS (14.00 g) containing no polymerization inhibitor prepared in Synthesis Example 2, the polar organic solvent DMSO (30.82 g), and 2-dimethylaminoethanol (1.25 g) were placed in a 100 ml glass sample bottle, sealed, and dissolved while stirring with a magnetic stirrer, and the stirring was continued at 25° C. Periodically sampling was performed and the polymer content was quantified by GPC measurement. As a result, as shown in Table 8, the polymer content in the solution after 14 days of curing was 0.01% by weight, and it was confirmed that the solution was stable despite the low water content and the absence of an organic polymerization inhibitor. This is believed to be due to the stabilizing effect of the amine.
[0092] Example 20 (Stability of AmSS in DMSO) The stability of the solution was confirmed under the same conditions as in Example 19, except that the amount of 2-dimethylaminoethanol added was reduced to 0.30 g. As a result, as shown in Table 8, the polymer content in the solution after 14 days of curing was 0.02% by weight, and it was confirmed that the solution was stable despite the low water content and the absence of an organic polymerization inhibitor.
[0093] The following investigation confirmed that 2-dimethylaminoethanol has no adverse effect on the AmSS polymerization process. AmSS, 2-dimethylaminoethanol, polymerization initiator AIBN (1.98 wt% DMSO solution) and DMSO were collected and dissolved in a 300 ml four-neck flask in the composition shown in Polymerization Examples 1 and 2 in Table 9, and then deoxygenated by repeatedly reducing pressure with an aspirator and introducing nitrogen. The solution was then immersed in a water bath at 75°C and polymerized while stirring with a stirrer. The polymerization solution was sampled periodically to track the polymerization conversion rate and molecular weight. As shown in Table 9, it is clear that even when 10 mol% of 2-dimethylaminoethanol was added to AmSS under conditions of a small amount of initiator added, there was no decrease in the polymerization rate or molecular weight. Note that the molecular weight exceeded the exclusion limit, so the peak top molecular weight was recorded.
[0094] Example 21 (Stability of AmSS in DMSO) Dry AmSS (14.00 g) containing no polymerization inhibitor prepared in Synthesis Example 2, the polar organic solvent DMSO (30.00 g), and N,N-dimethylcyclohexylamine (0.15 g) were placed in a 100 ml glass sample bottle, sealed, and dissolved while stirring with a magnetic stirrer, and then stirring was continued at 25° C. Periodically sampling was performed and the polymer content was quantified by GPC measurement. As a result, as shown in Table 9, the polymer content in the solution after 14 days of curing was 0.03 wt %, and it was confirmed that the solution was stable despite the low water content and the absence of an organic polymerization inhibitor.
[0095] Example 22 (Stability of AmSS in DMSO) The stability of the solution was confirmed under the same conditions as in Example 21, except that ion-exchanged water (1.50 g) was further added. As a result, as shown in Table 8, the polymer content in the solution after 14 days of curing was 0.02% by weight, and it was confirmed that the solution was stable despite the absence of an organic polymerization inhibitor. In addition, the reason why the stability was higher than that of Example 21 is thought to be due to the synergistic effect of the aliphatic amine and water.
[0096] Example 23 (Stability of AmSS in NMP) Dry AmSS (14.00 g) containing no polymerization inhibitor prepared in Synthesis Example 2, the polar organic solvent NMP (30.00 g), and N,N-dimethylcyclohexylamine (0.43 g) were placed in a 100 ml glass sample bottle, sealed, and dissolved while stirring with a magnetic stirrer, and the stirring was continued at 25° C. Periodically sampling was performed and the polymer content was quantified by GPC measurement. As a result, as shown in Table 8, the polymer content in the solution after 14 days of curing was 0.03 wt %, and it was confirmed that the solution was stable despite the low water content and the absence of an organic polymerization inhibitor.
[0097] Example 24 (Stability of AmSS in NMP) The stability of the solution was confirmed under the same conditions as in Example 23, except that the aliphatic amine in Example 23 was changed to N-methylmorpholine and 0.30 g was added. As a result, as shown in Table 8, the polymer content in the solution after 14 days of curing was 0.05% by weight, and it was confirmed that the solution was stable despite the low water content and the absence of an organic polymerization inhibitor.
[0098] [Table 8]
[0099] [Table 9] [Industrial Applicability]
[0100] The polar organic solvent solution of ammonium styrenesulfonate of the present invention is stabilized with a specific concentration of water and a minimum necessary amount of organic polymerization inhibitor, and spontaneous polymerization, which was a conventional problem, is suppressed. This makes it possible to stably and reproducibly produce pigment dispersants, hard coat materials, cation exchange membranes, and the like using ammonium styrenesulfonate, making the solution extremely useful industrially.
Claims
1. Ammonium styrene sulfonate, Water content of 300.0 mol% or less relative to ammonium styrenesulfonate; 20 mol % or less of an aliphatic amine relative to ammonium styrenesulfonate; 0.500 mol % or less of an organic polymerization inhibitor relative to ammonium styrenesulfonate; A polar organic solvent solution of ammonium styrenesulfonate, the spontaneous polymerization of which is inhibited, comprising:
2. Ammonium styrene sulfonate, Water of 100.0 mol % to 300.0 mol % relative to ammonium styrenesulfonate; 20.0 mol % or less of an aliphatic amine relative to ammonium styrenesulfonate; 0.0020 mol % to 0.500 mol % of an organic polymerization inhibitor relative to ammonium styrenesulfonate; 2. The solution of claim 1 comprising:
3. Ammonium styrene sulfonate, Water content of 300.0 mol% or less relative to ammonium styrenesulfonate; 1.0 mol % to 20.0 mol % of an aliphatic amine relative to ammonium styrenesulfonate; 0.500 mol % or less of an organic polymerization inhibitor relative to ammonium styrenesulfonate; 2. The solution of claim 1 comprising:
4. 2. The solution according to claim 1, wherein the content of ammonium styrenesulfonate is 20.0% by weight to 45.0% by weight based on the total amount of the solution.
5. 2. The solution of claim 1, wherein the content of spontaneously polymerized polymer is 0.5% by weight or less.
6. The solution according to claim 1, wherein the polar organic solvent has the following Hansen solubility parameters (a) to (c) in the following ranges: (a) Dispersion term δ d =16.5~18.5MPa 1/2 (b) Polar term δ p =11.5~16.5MPa 1/2 (c) Hydrogen binding term δ h = 7.0~12.5MPa 1/2
7. 2. The solution according to claim 1, wherein the polar organic solvent contains 80% by weight or more of one or more organic solvents selected from the group consisting of N-methylpyrrolidone, N-ethyl-2-pyrrolidone, dimethylsulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and 1,3-dimethyl-2-imidazolidinone.
8. The solution according to claim 1 , wherein the organic polymerization inhibitor is a phenol-based polymerization inhibitor and / or a stable nitroxyl-based polymerization inhibitor.
9. 2. The solution according to claim 1, wherein the aliphatic amine is an aliphatic amine having 8 or less carbon atoms.
10. The organic polymerization inhibitor is selected from the group consisting of 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 4-ethoxyphenol, 4-cyanophenol, 4-butoxyphenol, 3-ethoxyphenol, 2,5-dimethoxyphenol, 2,6-dimethoxyphenol, 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 4-tert-butylcatechol, hydroquinone, methylhydroquinone, 2-methoxyhydrazine, The solution according to claim 1, wherein the polymerization inhibitor is one or more selected from the group consisting of 2,2,6,6-tetramethylpiperidine 1-oxyl, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, 4-(2-hydroxypropoxy-3-(2-hydroxyethoxy))-2,2,6,6-tetramethylpiperidin-1-ol, and 4-(3-hydroxypropoxy-2-(2-hydroxyethoxy))-2,2,6,6-tetramethylpiperidin-1-ol.
11. The solution according to claim 1, wherein the aliphatic amine is one or more aliphatic amines selected from the group consisting of 2-hydroxyethylamine, diethylamine, diethanolamine, N-methylethanolamine, N-methyl-N,N-diethanolamine, piperidine, morpholine, N-methylpiperazine, triethylamine, triethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-dimethylcyclohexylamine, N-methylpiperidine, N-methylmorpholine, N-ethylmorpholine, and 2-[(2-dimethylamino)ethoxy]ethanol.
12. In the polar organic solvent solution of ammonium styrenesulfonate used in the polymerization process of ammonium styrenesulfonate, The water content of ammonium styrenesulfonate is 300.0 mol % or less, 20.0 mol% or less of aliphatic amine relative to ammonium styrenesulfonate; An organic polymerization inhibitor relative to ammonium styrenesulfonate is 0.500 mol % or less, A method for suppressing spontaneous polymerization of ammonium styrene sulfonate.
13. A solvent different from the polar organic solvent contained in the ammonium styrenesulfonate solution is added to the polar organic solvent solution to obtain a solvent composition having the following Hansen solubility parameters (d) to (f) in the following ranges, and then an oil-soluble vinyl monomer and a polymerization initiator are added to carry out radical copolymerization. Or, An oil-soluble vinyl monomer and a polymerization initiator are added to the polar organic solvent solution of ammonium styrenesulfonate, and then a solvent different from the polar organic solvent contained in the solution is added to obtain a solvent composition having the following Hansen solubility parameters (d) to (f) in the following ranges, and then radical copolymerization is performed. Method for producing ammonium styrene sulfonate copolymer. (d) Dispersion term δ d =17.5~18.5MPa 1/2 (e) Polarization term δ p =12.0~16.5MPa 1/2 (f) Hydrogen binding term δ h = 8.5~12.5MPa 1/2
14. The solvent different from the polar organic solvent is one or more solvents selected from the group consisting of ethylene glycol, propylene glycol, glycerin, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, methoxyethanol, ethoxyethanol, 1-methoxy-2-propanol, propylene glycol monomethyl ether, dioxane, dihydrolevoglucosenone, dimethoxyethane, triethanolamine, acetone, acetonitrile, and water. The production method according to claim 13.
15. The method for producing ammonium styrene sulfonate (AmSS) copolymer according to claim 13, wherein the oil-soluble vinyl monomer is one or more monomers selected from the group consisting of styrenes, acrylic acid esters, methacrylic acid esters, and maleimides.
Citation Information
Patent Citations
Apparatus for detecting metal
JP1984024282A
Curable composition and cured product thereof, hard coat material and hard coat film, and laminate
JP2016079363A
Ion exchange membrane with imprinted nonwoven substrate
JP7386705B2
Styrene sulfonate cation exchange membrane
US6221248B1